Maternal health care in India: some observations from RSOC, NFHS-3 and DLHS-3 - Muzaffar, Nadiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Maternal health is a key indicator of women’s health and status. Strengthening of maternal health care services is very important to ensure safe motherhood. The maternal health care services include antenatal care, natal care and postnatal care. Absence of proper maternal health care leads to various complications and eventually maternal death. World Health Organization, in its World Health Report 2005, suggests that poor maternal conditions account for the fourth leading cause of death for women worldwide, after HIV/AIDS, malaria, and tuberculosis. Situated within this background, this paper locates the status of maternal health care in India and identifies the changes that have occurred within the maternal health care services since last one decade. This paper is based on the secondary sources in general and the data provided by Rapid Survey on Children (RSOC 2013-14), District Level Household and Facility Survey (DLHS-3, 2007-08) and National Family Health Survey (NFHS-3, 2005-06) in particular. The data shows that maternal health care differs with the socio-cultural background like income, age, caste and place of residence. After having a comparison of the data provided by the three different surveys, it was observed that since the last decade the percentage of institutional deliveries has increased for both rural and urban areas. There has been an increase in the proportion of postnatal care received by women within 48 hours of discharge/ delivery. The Iron and Folic Acid (IFA) intake for 90 days or more has not improved by more than 0.5 percent. In India still about 30 percent women aged (20-24) married before the legal minimum marriage age of 18. Percentage of women receiving ANC from government health facility has decreased and for private facility it has increased when we compare the data from all the three surveys.